2016
DOI: 10.1038/srep27605
|View full text |Cite
|
Sign up to set email alerts
|

Advanced uracil DNA glycosylase-supplemented real-time reverse transcription loop-mediated isothermal amplification (UDG-rRT-LAMP) method for universal and specific detection of Tembusu virus

Abstract: Tembusu virus (TMUV) is a mosquito-borne flavivirus which threatens both poultry production and public health. In this study we developed a complete open reading frame alignment-based rRT-LAMP method for the universal detection of TUMV. To prevent false-positive results, the reaction was supplemented with uracil DNA glycosylase (UDG) to eliminate carryover contamination. The detection limit of the newly developed UDG-rRT-LAMP for TMUV was as low as 100 copies/reaction of viral RNA and 1 × 100.89 − 1 × 101.55 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 45 publications
1
25
0
1
Order By: Relevance
“… 25 Notably, conventional nucleic acid amplification approaches ( e.g. polymerase chain reaction (PCR), 26 strand displacement amplification (SDA), 27 , 28 rolling circle amplification (RCA), 25 and exponential isothermal amplification reaction (EXPAR) 29 ) are usually based on either DNA polymerase or the combination of nickase and DNA polymerase to produce large amounts of DNA fragments for the achievement of signal amplification, but they inevitably suffer from a high background signal caused by nonspecific amplification, because (1) some DNA polymerases have no proofreading exonuclease activity to repair the mismatched deoxyribonucleotides, 30 , 31 which leads to the generation of nonspecific fragments; (2) the DNA polymerase mediates ab initio synthesis 32 and the elongation of DNA duplexes in which the recognition site of nickase will be randomly incorporated, 33 which results in exponential amplification of nonspecific DNA. 34 To eliminate the high background signal, uracil-DNA glycosylase and endonuclease IV are introduced to coordinate with DNA polymerase to initiate uracil repair-mediated nucleic acid amplification, 34 , 35 but this enzymatic repair-based amplification (ERA) requires the coexistence of two repair enzymes ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“… 25 Notably, conventional nucleic acid amplification approaches ( e.g. polymerase chain reaction (PCR), 26 strand displacement amplification (SDA), 27 , 28 rolling circle amplification (RCA), 25 and exponential isothermal amplification reaction (EXPAR) 29 ) are usually based on either DNA polymerase or the combination of nickase and DNA polymerase to produce large amounts of DNA fragments for the achievement of signal amplification, but they inevitably suffer from a high background signal caused by nonspecific amplification, because (1) some DNA polymerases have no proofreading exonuclease activity to repair the mismatched deoxyribonucleotides, 30 , 31 which leads to the generation of nonspecific fragments; (2) the DNA polymerase mediates ab initio synthesis 32 and the elongation of DNA duplexes in which the recognition site of nickase will be randomly incorporated, 33 which results in exponential amplification of nonspecific DNA. 34 To eliminate the high background signal, uracil-DNA glycosylase and endonuclease IV are introduced to coordinate with DNA polymerase to initiate uracil repair-mediated nucleic acid amplification, 34 , 35 but this enzymatic repair-based amplification (ERA) requires the coexistence of two repair enzymes ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…sequent incubation of the reaction tubes at 65°C effectively inactivates the UDG enzyme and allowing the LAMP reaction to proceed. Tang et al (2016) has reported a UDGreal-time reverse transcription (rRT)-LAMP method for detection of Tembusu virus. LAMP amplicons were serial diluted with concentrations ranging from 0.5×10 -19 to 0.5×10 -14 g/µL, where it was found that rRT-LAMP without UDG can detect as little as 1×10 -18 g of simulated carryover contamination per reaction and showed that the addition of UDG can eliminate as much as 1×10 -16 g/per reaction of contaminants.…”
Section: Resultsmentioning
confidence: 99%
“…To prevent the forward contamination, dTTP was replaced by equal ratios of dTTP and dUTP, so that dUTP would be incorporated into RT-LAMP amplicons. This turns the possible contaminating amplicon into a substrate for uracil-DNA glycosylase (UDG) during the preparation of any subsequent RT-LAMP reactions 31,32 . When a thermolabile version of UDG is used, dU-containing amplicons can be digested at room temperature as the RT-LAMP samples are being set up, and the UDG will be inactivated during isothermal amplification.…”
Section: Representative Resultsmentioning
confidence: 99%